Theoretical Investigations of Interaction Between Boron Group Elements and Noble Gases with Charged Reactants in CO2 Photoreduction with H2O System - Luo, Dongmei; Kan, Wei; Zhang, Ning; Xiao, Wenmin; Zhang, Xiaofei (Asian Journal of Chemistry, 2013)
The interaction between boron group elements and noble gases with charged reactants has been investigated theoretically in the synthesis of methanol by photoreduction of CO2 with H2O. The different effects of boron group elements and noble gases have been calculated at MP2 level. Noble gas atoms interacted with H2O+ and the third main-group elements interacted with CO2•−. Our results revealed that boron group elements might maintain the structure of CO2•− like CO32–, which is convenient for appropriate radicals reacting with CO2•− to form the aim product or its precursor, therefore the electron-defect atom is advantageous to the reaction herein. It is interesting that the rare gas elements tend to inert H2O+ to the structure of H2O. The excited state parameters showed that Ga, Kr and Xe are beneficial to the photoreduction of CO2 with H2O.